Natural resource management in the hillsides of Honduras: bioeconomic modeling at the micro-watershed level - Barbier, Bruno; Bergeron, Gilles (International Food Policy Research Institute, 2001)
Barbier and Bergeron explore several hypotheses about the dynamics of natural resource management in the hillsides of La Lima and further explore the causes and consequences of the transition to vegetable production. To fully integrate agroecological factors, such as forest, water resources, and topography, the authors use a bioeconomic model that links farmers’ resource management decisions to biophysical models. This captures production processes as well as the condition of natural resources. The model was used to run different scenarios over the period 1975 to 1995 and then to project into the future. The authors conclude that agroecological conditions are the most important factors de-termining incomes for villages with comparable agroecological conditions.